EVALUASI SUPERVISI PENGAJARAN PENDIDIKAN AGAMA KATOLIK (Studi Multi Kasus di SMP Katolik dan SMP Negeri Se-Kecamatan Kota Kefamenanu, Kabupaten TTU, Provinsi NTT) - Usboko, Wilibrodus Cornelis (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2021)
This study aims to determine the understanding of the meaning of the evaluation of teaching supervision of Catholic religious education, the objectives and principles of evaluating the supervision of Catholic religious education teaching, the evaluation methods of teaching supervision of Catholic religious education, the aspects evaluated in the supervision of Catholic religious education teaching, and the results obtained from the evaluation of teaching supervision activities for Catholic religious education. This study used a qualitative method with a multi-case study type. Data were collected through interviews, observations, documentation studies, and conceptually inductive analysis. The results obtained were the inequality of concepts regarding understanding between one school and another about the meaning, objectives and principles, methods, aspects that were evaluated, and the results obtained from the evaluation of the supervision of Catholic religious education teaching. It was found that there were supervisors who really understood the concept of evaluating teaching supervision correctly, but there were also those who lacked or even misunderstood the concept of evaluation of teaching supervision in question.